The Correlation Between Parental Support and Adolescent Girls’ Readiness for Menarche at Sdn Wiradadi Banyumas - Khoeronisa Maulidhia; Murniati; Siti Haniyah (Viva Medika, 2024)
The early onset of menarche can be a frightening event for adolescents who are not prepared. Menarche is a crucial stage for adolescent girls. Therefore, parents should play a role in understanding about menarche. This study aims to determine the relationship between parental support and the readiness of fifth and sixth-grade adolescent girls to face menarche at Wiradadi Public Elementary School. The research method used is correlational, with a cross-sectional approach. This study involved 50 respondents, consisting of fifth and sixth-grade female students who have not experienced menarche at Wiradadi Public Elementary School, selected through the total sampling technique. The statistical test used is the Spearman rank test. The results of this study indicate that the majority of respondents are aged 11 years (48%), have good parental support (35.6%), and have high readiness (42.2%). The research results show a relationship between parental support and the readiness of adolescent girls to face menarche at Wiradadi Public Elementary School, with a moderate strength of relationship (p-value: 0.001; CC = 0.457). In conclusion, there is an average and positive relationship between parental support and the readiness of adolescent girls.